Toward strategical bottom-up synthesis of carbon materials with exceptionally high pyridinic-nitrogen content: Development of screening techniques. (15th October 2022) - Yamada, Yasuhiro; Tanaka, Haruki; Tanaka, Yosuke; Kubo, Shingo; Taguchi, Taisei; Sato, Satoshi
Abstract: Selective doping of nitrogen-containing functional groups of carbon materials is the most essential technique for enhancing properties significantly for various applications such as catalysts and electrodes. Reported carbon materials with controlled pyridinic nitrogen are generally synthesized on substrates, leading to low productivity and high cost. Thus, simple preparation methods for selective doping of nitrogen in carbon materials without substrates are indispensable for mass production. This work discovered that simple heat treatment of 1, 7-phenanthroline at 973 K formed carbon material with exceptionally high pyridinic nitrogen content (92%). The selective doping of pyridinic nitrogen was attained by the protection of pyridinic nitrogen due to the steric hindrance by the neighboring C–H group on armchair edges to avoid the formation of N–H bonding on pyridinic nitrogen on armchair edges. Screening techniques of precursors for preparing carbon materials with high pyridinic nitrogen content are also essential to minimize research costs. Screening by 1) formation energy of hydrogenation on pyridinic nitrogen, 2) molecular dynamic simulation with reactive force field, and 3) comparison of structures of precursors revealed that 1, 7-phenanthroline was the best precursor to maintain the high percentage of pyridinic nitrogen after carbonization. Thus, strategic synthesis is now possible using screening techniques. Graphical abstract: Image 1